Evolutionary analysis of the OSCA gene family in sunflower (Helianthus annuus L) and expression analysis under NaCl stress - Shan,Feibiao; Wu,Yue; Du,Ruixia; Yang,Qinfang; Liu,Chunhui; Wang,Yongxing; Zhang,Chun; Chen,Yang (PeerJ, 2023)
Hyperosmolality-gated calcium-permeable channels (OSCA) are Ca2 + nonselective cation channels that contain the calcium-dependent DUF221 domain, which plays an important role in plant response to stress and growth. However, the OSCA gene has not been fully identified and analyzed in sunflowers. In this study, we comprehensively analyzed the number, structure, collinearity, and phylogeny of the OSCA gene family in the sunflower, six Compositae species (Arctium lappa, Chrysanthemum morifolium, Cichorium endivia, Cichorium intybus, Lactuca sativa var. Angustata, and Carthamus tinctorius), and six other plants (soybean, Arabidopsis thaliana, rice, grape, and maize). The expression of the sunflower OSCA gene in nine different tissues, six different hormones, and NaCl stress conditions were analyzed based on transcriptome data and qRT–PCR. A total of 15 OSCA proteins, distributed on 10 chromosomes, were identified in the sunflower, and all of them were located in the endoplasmic reticulum. Using the phylogenetic tree, collinearity, gene structure, and motif analysis of the six Compositae species and six other plants, we found that the sunflower OSCA protein had only three subfamilies and lacked the Group 4 subfamily, which is conserved in the evolution of Compositae and subject to purification selection. The OSCA gene structure and motif analysis of the sunflower and six Compositae showed that there was a positive correlation between the number of motifs of most genes and the length of the gene, different subfamilies had different motifs, and the Group 4 subfamily had the smallest number of genes and the simplest gene structure. RNA-seq and qRT–PCR analysis showed that the expression levels of most OSCA genes in the sunflower changed to varying degrees under salt stress, and HaOSCA2.6 and HaOSCA3.1 were the most important in the sunflower’s response to salt stress. The coexpression network of the sunflower genes under salt stress was constructed based on weighted gene co-expression network analysis (WGCNA). In conclusion, our findings suggest that the OSCA gene family is conserved during the sunflower’s evolution and plays an important role in salt tolerance. These results will deepen our understanding of the evolutionary relationship of the sunflower OSCA gene family and provide a basis for their functional studies under salt stress.
Keywords: Sunflowers; OSCA gene family; Evolutionary analysis; Expression analysis; Coexpression network